2023
DOI: 10.1029/2023jd039636
|View full text |Cite
|
Sign up to set email alerts
|

Mesospheric Temperature and Circulation Response to the Hunga Tonga‐Hunga‐Ha'apai Volcanic Eruption

Wandi Yu,
Rolando Garcia,
Jia Yue
et al.

Abstract: The Hunga Tonga Hunga‐Ha'apai (HTHH) volcanic eruption on 15 January 2022 injected water vapor and SO2 into the stratosphere. Several months after the eruption, significantly stronger westerlies, and a weaker Brewer‐Dobson circulation developed in the stratosphere of the Southern Hemisphere and were accompanied by unprecedented temperature anomalies in the stratosphere and mesosphere. In August 2022, the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) satellite instrument observed record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…While most of the H 2 O + SO 2 ensemble members show relative cold temperatures and weak wave fluxes, there is considerable stochastic variability among the realizations, and several realizations (6 out of 10) have temperature anomalies comparable to the observed 2022 anomalies. We conclude that internal variability in the ensemble model simulations contributes to the low bias in ensemble average temperature anomalies in Figure 4 compared to the observed pattern in 2022 (Yu et al, 2023). In spite of this difference in magnitude, the similarity in timing and spatial structure of observed and modeled temperature patterns is strongly suggestive of an HTHH attribution for the observed anomalies.…”
Section: Temperature Perturbationmentioning
confidence: 63%
See 1 more Smart Citation
“…While most of the H 2 O + SO 2 ensemble members show relative cold temperatures and weak wave fluxes, there is considerable stochastic variability among the realizations, and several realizations (6 out of 10) have temperature anomalies comparable to the observed 2022 anomalies. We conclude that internal variability in the ensemble model simulations contributes to the low bias in ensemble average temperature anomalies in Figure 4 compared to the observed pattern in 2022 (Yu et al, 2023). In spite of this difference in magnitude, the similarity in timing and spatial structure of observed and modeled temperature patterns is strongly suggestive of an HTHH attribution for the observed anomalies.…”
Section: Temperature Perturbationmentioning
confidence: 63%
“…The vertical structure of the temperature anomalies averaged over 60°S-10°S (Figure 4b) shows cooling covering much of the mid-stratosphere throughout 2022, with largest cold anomalies during SH winter (June-August) extending to ∼45 km. During these months there are anomalous warm temperatures in the lower mesosphere above ∼50 km (Yu et al, 2023, see Section 3.3). Cold anomalies are reduced in 2023.…”
Section: Temperature Perturbationmentioning
confidence: 92%
“…Trends in ELR power are evaluated from the time series of globally integrated annual power values from 2002 through 2021. The year 2022 is not included in the analysis due to the unprecedented effects on the thermal structure of the upper MLT due to the eruption of Hunga Tonga-Hunga Ha'apai (Yu et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Manney et al (2023) showed that the H 2 O plume did not affect the 2022 Antarctic vortex, and Santee et al (2023) showed that while the sulfate aerosol did result in some heterogeneous processing, it did not lead to appreciable chemical ozone loss. Yu et al (2023) showed 2022 temperature anomalies from SABER in the stratosphere and mesosphere and concluded, based on WACCM6 calculations, that these could, to some extent be explained by changes in stratospheric winds, possibly driven by changes in H 2 O and SO 2 from the Hunga plume. Fleming et al (2024) have presented some calculations of the effect of this additional H 2 O on O 3 and temperature over the next decade.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al. (2023) showed 2022 temperature anomalies from SABER in the stratosphere and mesosphere and concluded, based on WACCM6 calculations, that these could, to some extent be explained by changes in stratospheric winds, possibly driven by changes in H 2 O and SO 2 from the Hunga plume. Fleming et al.…”
Section: Introductionmentioning
confidence: 99%